Multifunctional nanoparticle-VEGF modification for tissue-engineered vascular graft to promote sustained anti-thrombosis and rapid endothelialization - Liu, Yalin; Yuan, Haoyong; Liu, Yuhong; Chen, Chunyang; Tang, Zhenjie; Huang, Can; Ning, Zuodong; Lu, Ting; Wu, Zhongshi (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: The absence of a complete endothelial cell layer is a well-recognized reason leading to small-diameter tissue-engineered vascular graft failure. Here we reported a multifunctional system consisting of chitosan (CS), Arg-Glu-Asp-Val (REDV) peptide, heparin, and vascular endothelial growth factor (VEGF) to achieve sustained anti-thrombosis and rapid endothelialization for decellularized and photo-oxidized bovine internal mammary arteries (DP-BIMA). Methods: CS-REDV copolymers were synthesized via a transglutaminase (TGase) catalyzed reaction. CS-REDV-Hep nanoparticles were formed by electrostatic self-assembly and loaded on the DP-BIMA. The quantification of released heparin and VEGF was detected. Hemolysis rate, platelets adhesion, endothelial cell (EC) adhesion and proliferation, and MTT assay were performed in vitro. The grafts were then tested in a rabbit abdominal aorta interposition model for 3 months. The patency rates were calculated and the ECs regeneration was investigated by immunofluorescence staining of CD31, CD144, and eNOS antibodies. Results: The nanoparticle-VEGF system (particle size: 61.8±18.3 nm, zeta-potential: +13.2 mV, PDI: 0.108) showed a sustained and controlled release of heparin and VEGF for as long as 1 month and exhibited good biocompatibility, a lower affinity for platelets, and a higher affinity for ECs in vitro. The nanoparticle-VEGF immobilized BIMA achieved 100% and 83.3% patency in a rabbit abdominal interposition model during 1 month and 3 months, respectively, without any thrombogenicity and showed CD31, CD144, eNOS positive cell adhesion as early as 1 day. After three months, CD31, CD144, and eNOS positive cells covered almost the whole luminal surface of the grafts. Conclusion: The results demonstrated that the multifunctional nanoparticle-VEGF system can enhance the anti-thrombosis property and promote rapid endothelialization of small-diameter tissue-engineered vascular grafts. Utilizing nanoparticles to combine different kinds of biomolecules is an appropriate technology to improve the long-term patency of small-diameter tissue-engineered vascular grafts.